2008
DOI: 10.3406/paleo.2008.5255
|View full text |Cite
|
Sign up to set email alerts
|

The Plastered Skulls and Other PPNB Finds from Yiftahel, Lower Galilee (Israel)

Abstract: Two extended seasons of excavations were recently conducted at the site of Yiftahel (Khalet Khalladyiah) in the fringe of Beit Netofa valley, Lower Galilee. Four new areas (F, G, H and I) were opened in addition to the five areas excavated in the past. This note will present the highlights from the main occupational period at Yiftahel, i. e., the Mid-Late PPNB (8,000-7,000 BC). Large PPNB buildings, displaying rectilinear plan with mud-brick and/ or stone walls, were discovered in the recent seasons of excavat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 1 publication
2
14
0
3
Order By: Relevance
“…The fact that the two similar masks bracket the one different wide-faced mask brings forth a sense of symmetry or harmony, which may reflect both spiritual and aesthetical purposes, and thus could have been intentional. This rare find can be hypothesized to hold a discrete meaning, such as the representation of two distinct classes of people, as was suggested previously [3]. Moreover, in this case, the fact that Homo 1 and Homo 3 are putatively younger than Homo 2 may have had an impact on the choice of mask type, as well as on their positioning on both sides of Homo 2.…”
Section: Discussionsupporting
confidence: 62%
“…The fact that the two similar masks bracket the one different wide-faced mask brings forth a sense of symmetry or harmony, which may reflect both spiritual and aesthetical purposes, and thus could have been intentional. This rare find can be hypothesized to hold a discrete meaning, such as the representation of two distinct classes of people, as was suggested previously [3]. Moreover, in this case, the fact that Homo 1 and Homo 3 are putatively younger than Homo 2 may have had an impact on the choice of mask type, as well as on their positioning on both sides of Homo 2.…”
Section: Discussionsupporting
confidence: 62%
“…This is exemplified by the site of Yiftahel (Lower Galilee, Israel), where large tracts of plaster floors were preserved in several different stratigraphie levels (Garfinkel 1987;Ronen et al 1991;Marder et al 2008;Milevski et al 2008). Nearly 2000 m 2 have been excavated by archaeological and salvage expeditions over the last 25 yr, and these investigations have shown that the PPNB stratigraphy can be quite different from area to area.…”
Section: Introductionmentioning
confidence: 99%
“…est fabriqué sur des lames bipolaires. La TLB atteint des niveaux élevés de savoir-faire (artisanat) où certains sites sont interprétés comme centres régionaux de production spécialisée (Yiftael et 'Ain Ghazzal par exemple) exportant une partie de leur production vers d'autres localités (Milevski et al 2008). Le Néguev, en revanche, constitue l'exception à la règle puisque quelques auteurs proposent l'existence d'un système local différent : le « single dominant platform » ( Figure 11C) (Barzilai 2013;Barzilai & Goring-Morris 2011).…”
Section: Variantes Et Diffusionunclassified
“…Par conséquent, il apparaît nécessaire de repenser si, et dans quelles circonstances les technologies bipolaires peuvent être envisagées comme productions spécialisées. En guise d'exemple, il a été proposé, dans le sud du Levant, que des centres de production spécialisée ('Ain Ghazal et Yiftahel par exemple) ont exporté une partie de leur production vers d'autres localités (Milevski et al 2008;Quintero 2010). Les principaux arguments d'une telle interprétation sont la quantité des productions (massive) ainsi que les niveaux élevés de savoir-faire et de standardisation atteints sur ces sites.…”
Section: Est-ce Une Production Spécialisée ?unclassified